Mechanical behavior of palm kernal shell concrete - Che Muhammad Faris, Che Mohd Shamshudin (2015)
Palm kernel shell is a waste which is abundantly generated and disposed at the landfill by Malaysian palm oil industry. As a result, it contributes toward pollution problem. Using palm kernel shell as partial course aggregate replacement with different in concrete making would be able to reduce the amount of this waste ending up at landfill. This thesis presents an experimental study on the workability, compressive strength and flexural strength. Two types of mixes are prepared. One consists of a control mix and another one consist various sizes of crushed palm kernel shell with fixed percentages replacement. The sizes of palm kernel shell are 2.36mm-5mm,5mm-10mm and 10mm-15mm.The influenced of with palm kernel shell several sizes on the properties of concrete have been investigated. The workability decrease with an increase in the size of palm kernel shell used and compressive strength at size 5mm-10mm has a good strength. Flexural test increase with increase the size of palm kernel shell